Qalandar-name. Chapter 4. “Praising ‘Umar, Commander of the Faithful” » - M.R. Ismagilova; D.A. Shagaviev (Золотоордынское обозрение, 2015)
The presented fragment is the next part of the translation of the medieval poetic text “Qalandar-name” written by Abu Bakr Qalandar, the Sufi scholar from the Crimea. This Chapter is devoted to praises to ‘Umar ibn Khattab al-Faruq (The Distinguish), the Successor of the Prophet Muhammad, the second of the four Righteous Caliphs (al-Khulafa al-Rashidun). Within the nine rows the author mentions the virtues of ‘Umar making the main emphasis on his active support for Islam and justice for people. The Persian text is translated by Milyausha Ismagilova, the postgraduate student. The translation’s edition and comments are supplied by Damir Shagaviev, Head of the Department of History of Religions and Social Thought at the Sh.Marjani Institute of History of AS RT (Kazan). * Continuation. See the beginning in: Golden Horde Review, 2014, № 2(4), pp. 243–252; № 3(5), pp. 207–214; №4(6), pp. 198–207. Russian translation from Persian by a graduate student M.R. Ismagilova. Academic edition of the translation and comments by D.A. Shagaviev, Head of the Department of History of Religions and Social Thought at the Sh.Marjani Institute of History of AS RT (Kazan).